INFLUENCE OF MICROFINANCE SERVICES ON WOMEN BUSINESS PERFORMANCE IN VILLUPURAM DISTRICT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Microfinance is defined as a development tool that grants or provides financial services and products such as very small loans, savings, micro-leasing, micro-insurance and money transfer to assist the very or exceptionally poor in expanding or establishing their businesses. The sample size of the research was 50 women entrepreneurs. Simple random sampling technique is used. The analysis discovered that there is influence of microfinance training and microfinance loan on women business performance. It is also identified there is influence of women business performance on growth of small business enterprises. Hence, it is concluded that the microfinance institutions many schemes to support women’s entrepreneurship but the awareness on those programs among the women entrepreneurs are not up to the appreciable level. The gap between the government policy and its implementation will be reduced with the help of appropriate promotional measures. Hence, the training authorities are advised to perform many awareness programs to develop the awareness on the different government schemes related to the women entrepreneurs.